Implementation of Factor Method for Determining Service Life of Exterior Paint for Building (Case Study: Bencoolen Mall, in Bengkulu) - Maharani, Dwi Jenita; Burnama, Nabila Siti; Guci, Jeply Murdiaman (Journal of Civil Engineering and Planning (JCEP), 2025)
Building maintenance and care are essential responsibilities that must be managed effectively to ensure optimal building performance and appearance. One of the key aspects of building maintenance is painting. Painting not only enhances the visual appeal of a building but also contributes to its overall preservation. However, paint has a limited lifespan and resistance to fading or deterioration. The decline in paint quality often occurs before reaching its expected durability due to various environmental and social factors such as humidity, rainfall, wind, dust, sunlight, and human activity. Therefore, understanding the service life of exterior paint is crucial to ensure timely maintenance and upkeep of the building. A study was conducted on the existing exterior paint of the Bencoolen Mall building, located at Jl. Pariwisata No. 01, Bengkulu City. The purpose of this study was to determine the service life of the building’s exterior paint. The method used in this research was the factor method, which involves calculating the Estimated Service Life (ESL) based on known environmental factors and Reference Service Life (RSL) values. The results of the study indicated that the estimated service life of the building's exterior paint, using the factor method, is approximately 8.56 years. Based on these findings, it is recommended that periodic inspections and maintenance be conducted approximately every 8 years to ensure the exterior paint remains in good condition.